Sustainable practices impacting employee engagement and well-being - Mendes, T.; Pereira, L.; Gonçalves, R.; Dias, Á.; Lopes da Costa, R. (Progress in Industrial Ecology, 2022)
As sustainability grows in importance and plays an increasingly critical role in our everyday life, it becomes relevant to understand how the implementation and embeddedness of sustainable practices across organisations impact the employee-organisation relationship. The present study aims to explore the direct effect of perceived organisational support toward the environment on the employee engagement levels and subjective well-being as well as to assess to which extent employee engagement impacts employee subjective well-being. The data collection process was carried out through a questionnaire from which resulted a cross-national sample of 230 employed individuals. The data was analysed through structural equation modelling and multiple linear regressions were conducted, allowing the identification and detailed description of relationships among the constructs. From the analysis, it was possible to conclude that perceived organisational support toward the environment has a positive significant effect on employee engagement levels. The results also show that contrarily to what was hypothesised; there is no direct significant positive effect from perceived organisational support toward the environment on employees' subjective well-being. Lastly, the results also concluded that employee engagement had a significantly strong positive effect on the employees' subjective well-being levels.